Detection of factor VIII and D-dimer biomarkers for venous thromboembolism diagnosis using electrochemistry immunosensor - Yokomichi, Anna Laura Yuri; Rodrigues, Valquiria da Cruz; Moroz, Andrei [UNESP]; Bertanha, Matheus [UNESP]; Ribeiro, Sidney J. L. [UNESP]; Deffune, Elenice [UNESP]; Moraes, Marli L. (Elsevier B.V., 2020)
Venous thromboembolism (VTE) is a serious clinical condition which early and accurate diagnosis may contribute to the reduction of associated morbidity and mortality. VTE occurs when a blood clot (thrombus) blocks the vein blood flow causing deep vein thrombosis (DVT) and, when it migrates to the lungs, it may clog the pulmonary arteries characterizing pulmonary embolism (PE). Analysis using fibrin degradation products or D-dimer and coagulation factor VIII may assist early diagnosis of VTE. Thus, two immunosensors were built using layer-by-layer (LbL) films technique, one containing the anti-D-dimer immobilized on polyethylene imine (PEI) and another the anti-FVIII on silk fibroin (SF). Immunosensor response, the antigen-antibody specific interaction, was investigated using cyclic voltammetry. When immunosensors, PEI/anti-D-dimer and SF/anti-FVIII, were exposed to antigens, D-dimer and Factor VIII, the voltammograms area and current were significantly increased with increasing specific antigen concentration. The specific interaction was confirmed with control experiments, electrodes containing only PEI or SF, that no significant changes in the voltammogram responses were observed and principal component analysis confirmed these results. The films formation and response were verified using scanning electronic microscopy (SEM). The developed immunosensor seems to be a promising and effective early complementary exam to assist in the VTE diagnosis, through the combined response of two biomarkers very sensible.
Keywords: Venous thromboembolism; Immunosensor; Factor VIII; Fibrin degradation products; D-dimer; Diagnosis; Voltammetric sensors